UNIVERSITY IMAGE FORMATION THROUGH THE PRISM OF SPORTS PR-COMMUNICATIONS - Yaremenko, Vadym (Global Prosperity, 2022)
PR-communications, used by universities’ management and innovation structures to form a positive image of the educational institution, are analyzed. The main focus is on the sports aspects of PR communications, which appear to be a different, clearly structured industry that operates to make the audience interested. The main techniques used in forming the university image are considered from the angle of separation and specification of technological methods to present the material in the context of the functioning of sports PR communications. To generalize and systematize the material related to the functioning of sports PR-communications, the supply of sports PR-communications by the site of Sumy State University was analyzed. At the end of the article, the results of the research are summarized.